Pengajaran ESP Bagi Polisi Pariwisata di Sekolah Tinggi Polda Bali - I Gusti Ayu Agung Dian Susanthi; I Made Astu Mahayana; Ni Nyoman Kertiasih (Linguistic Community Services Journal, 2020)
This study focuses on the language functions used and the frequency of occurrence of language functions in the teaching of tourism police at Bali Police State School. The language used is classified into several functions. According to Leech (1993), language functions are classified into five functions, namely: informative, expressive, directive, aesthetic, and fatigue functions. Meanwhile, according to Blundell (1978) expressions can be 'greetings', 'introductions', 'ask questions', and so on. However, based on the tour police conversation, the theory must be presented based on the procedures applied during the tourism police conversation, so that it can be applied in practice. This study applied lecture, pair work and conversation methods. As a result teaching, ESP to tourism police candidates needs to be given, considering the tourism police candidates will face directly with foreign tourists in the field. The introduction to ESP is still seldom to be given. Thus, it is considered necessary to be given a more frequent introduction by providing initial training to the tourism police candidates. This is expected to help tourism police candidates who initially only get general English lessons can develop with ESP material specifically for tourism police candidates.